THE ROLE OF GREEN ECONOMY, SUSTAINABLE HALAL ENVIRONMENT, AND DIGITAL TOURISM ON COMMUNITY INCOME: A CASE STUDY IN WEST JAVA AND LAMPUNG TOURISM VILLAGES - Anggraeni, Erike; Normasyhuri, Khavid; Kurniawan, Muhammad; Pramudita Wisnu Kusuma, Tri Atmaja (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
This study aims to investigate the influence of green economy, sustainable halal environment, and digital tourism on the community income in West Java and Lampung tourism villages. There was a total of 500 respondents participated in this quantitative study through a random sampling technique. The data was collected using a questionnaire measured using a 5-point Likert scale and analyzed using SmartPLS 3.0. The results show that the green economy, sustainable halal environment, and digital tourism have a positive and significant influence on the community income. Further, this study highlights that the digital tourism is able to positively moderate the influence of both green economy and sustainable halal environment on the community income. These findings imply that the developing innovative sustainable tourism business models not only increases the income of tourist village communities but also preserves the environment and promotes social inclusion. This offers valuable guidance for optimizing the economic benefits of tourism while minimizing its negative impacts on the environment and local communities.JEL: Z3.